University of Illinois Chorale [v.1] - University of Illinois Chorale; Stolzfus, Fred; Wustman, John
Resumen: Conferencia Nacional organizada por American Choral Directors Association en donde se presenta University of Illinois Chorale
Contiene: Missa De Beata Virgine / Josquin Desprez--Quartette für sopran, Alt, Tenor und bass mit pianoforte / Johannes Brahms--Trois chansons bretonnes / Henk Badings